Grebeg Sudiro as a form of Harmonization of Ethnic Javanese and Ethnic Chinese in Sudiroprajan Village, Surakarta - Muhammad, Ammar (Proceeding International Conference on Science and Engineering, 2020)
Local wisdom is a form of the culture of the past should be continuously used as a handle for a living. Culture in Indonesia since ancient times become habit in behave in society. The existence of the culture surrounding this society will bring a unity in diversity and become its own characteristics within the community. For example, as we will describe are Grebeg Sudiro which is acculturation of Javanese and Chinese culture. This research uses qualitative-descriptive research methods. The purpose of the use of this method is to uncover the facts, circumstances, phenomenon, variable, and circumstances that occur when doing research. The source we got using the method of interview, observation and literacy. Grebeg Sudiro was a tradition of celebration to welcome the Chinese new year or Imlek in Surakarta, Central Java. Grebeg Sudiro was born as a form of preservation of harmony between ethnic happens in Kampung Sudiroprajan. Grebeg Sudiro contains a number of activities, such as the ceremony of the Umbul Mantram, the Carnival culture, race copyright Creations Lanterns, decorative River boat tour of Pepe, bazar, Sudiroprajan and potential on the cover with the celebration Fireworks.